Casimir operator dependences of nonperturbative fermionic QCD amplitudes - Fried, H. M.; Grandou, Thierry; Hofmann, Ralf (International journal of modern physics. A, Particles and fields, gravitation, cosmology, 2016)
In eikonal and quenched approximations, it is argued that the strong coupling fermionic QCD Green’s functions and related amplitudes depart from a sole dependence on the SUc(3)SUc(3)SUc(3) quadratic Casimir operator, C2fC2fC2f, evaluated over the fundamental gauge group representation. Noted in nonrelativistic quark models and in a nonperturbative generalization of the Schwinger mechanism, an additional dependence on the cubic Casimir operator shows up, in contradistinction with perturbation theory and other nonperturbative approaches. However, it accounts for the full algebraic content of the rank-2 Lie algebra of SUc(3)SUc(3)SUc(3). Though numerically subleading effects, cubic Casimir dependences, here and elsewhere, appear to be a signature of the nonperturbative fermionic sector of QCD.